2009
DOI: 10.1038/ncb1883
|View full text |Cite
|
Sign up to set email alerts
|

The FANC pathway and BLM collaborate during mitosis to prevent micro-nucleation and chromosome abnormalities

Abstract: Loss-of-function of caretaker genes characterizes a group of cancer predisposition diseases that feature cellular hypersensitivity to DNA damage and chromosome fragility; this group includes Fanconi anaemia and Bloom syndrome. The products of the 13 FANC genes (mutated in Fanconi anaemia), which constitute the 'FANC' pathway, and BLM (the RecQ helicase mutated in Bloom syndrome) are thought to collaborate during the S phase of the cell cycle, preventing chromosome instability. Recently, BLM has been implicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
354
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 290 publications
(376 citation statements)
references
References 31 publications
22
354
0
Order By: Relevance
“…In the absence of these proteins a nuclease activity involving Mre11 degrades the regressed fork leading to the generation of broken ends and genomic instability. Finally, FA proteins are also localized to the anaphase bridges, where they cooperate with the DNA helicase BLM in the resolution of these structures [49,50]. All of the above indicate a key role for the FA pathway in the suppression of RS and replication-borne genomic instability.…”
Section: Rs As a Fuel Of Tumorogenesismentioning
confidence: 95%
See 1 more Smart Citation
“…In the absence of these proteins a nuclease activity involving Mre11 degrades the regressed fork leading to the generation of broken ends and genomic instability. Finally, FA proteins are also localized to the anaphase bridges, where they cooperate with the DNA helicase BLM in the resolution of these structures [49,50]. All of the above indicate a key role for the FA pathway in the suppression of RS and replication-borne genomic instability.…”
Section: Rs As a Fuel Of Tumorogenesismentioning
confidence: 95%
“…Additionally, they work on fork regression and restoration of chicken foot structures to normal forks that may be generated by lesions such as ICL [53]. In fact, the absence of these proteins increases genome instability as reflected by the expression of common fragile sites, along with increased sister chromatid exchanges and anaphase bridges [49,50,54]. Defects in BLM, WRN and RECQL4 cause Bloom, Werner and Rothmund-Thomson syndromes, respectively, which are associated with cancer and accelerated ageing phenotypes.…”
Section: Rs As a Fuel Of Tumorogenesismentioning
confidence: 99%
“…17 In favor of this last hypothesis, it has been recently suggested that sister chromatid disjunction at the NPM origin is frequently incomplete in human cells, but Fanconi proteins and BLM play a cooperative role in resolving these DNA links. 9,10 However, this pathway seems to be at least partially functional in MKs, as both This abnormality corresponds to nucleoplasmic bridges (NPM), as staining with TOTO revealed the presence of DNA. Sometimes, the connection was so thin that TOTO staining was not obvious but could be observed after overexposing the images ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…treatment with the DNA polymerase inhibitor aphidicolin). The Fanconi anemia proteins, FANCI and FANCD2 associate with CFSs after replication stress and localize to the termini of FS-UFBs [8,12–14]. Finally, telomeric UFBs (T-UFBs) can be induced by interfering with the replication of telomeres or by overexpression of the shelterin component TRF2 that induces chromosome end-to-end fusions [15–17].…”
Section: Introductionmentioning
confidence: 99%